Adenoidectomy may decrease the need for a third set of tympanostomy tubes in children. (June 2022) - Hancock, Sarah; Allen, Paul; Dixon, Angel'Niqua; Faria, John; Vandjelovic, Nathan; McKenna Benoit, Margo
Abstract: Objective: To determine whether removing or retaining adenoids at the time of placement of a second set of ear tubes impacts the need for a third set of ear tubes later in childhood. Study design: Single-institution retrospective case series. Setting: Tertiary academic university hospital. Methods: We identified pediatric subjects who had undergone a second ear tube placement between 1/1/17 and 9/1/19. Subjects were stratified into two groups: 1) adenoids removed at time of second tympanostomy tube insertion (TT+A) and 2) adenoids retained at time of second tympanostomy tube insertion (TT-A). A subset of children less than age 4 was also studied independently. The primary outcome was number of patients requiring a third set of tympanostomy tubes. Results: A total of 136 subjects met inclusion and exclusion criteria. Among children less than 4 years of age (n = 99), the incidence of requiring a third set of tubes was significantly lower in the TT+A group <4 (12.8%; 6/47) compared to the TT-A group <4 (44.2%; 23/52) (p = 0.0008) with an odds ratio of 0.18 (95%CI 0.067–0.51) and number needed to treat of 3.2. Conclusion: Performing adenoidectomy in children less than 4 years of age at the second tympanostomy procedure was associated with a reduced incidence of requiring a third set of ear tubes. Highlights: Retrospective chart review of 136 children who had received at least two sets of ear tubes. Incidence of ear tube reinsertion compared among children with and without adenoidectomy at time of second tube insertion. Not removing adenoids at time of second set of ear tubes increases risk of needing third set of ear tubes. The protective effect of adenoidectomy at second ear tube insertion was persistent even for children <4 years of age.